A Study on FeII, ZnII and CuII Complexes with Novel Tridentate Bis(pyrazolyl)methane Ligands. Issue 23 (22nd August 2018) - Herber, Ulrich; Moegling, Julian; Siris, Rita; Hoffmann, Alexander; Mayer, Peter; Göbel, Christoph; Lochenie, Charles; Weber, Birgit; Herres‐Pawlis, Sonja
Abstract : The ligand class of tridentate bis(pyrazolyl)methanes was extended via the syntheses of HC(3, 5‐EtPz)2 Py. This ligand is the first of its kind with a homogeneous 3, 5‐functionalization with large substituents. On the basis of 3, 5‐functionalized ligands we were able to synthesize 15 novel complexes with Fe II, Zn II, and Cu II salts. Herein we present an extensive coordination chemistry study, that focuses on the influences of different metals, ligands, and counterions on the coordination mode and on the spin state in case of Fe II complexes. Abstract :